Benefit‐Cost Analysis of Integrated Water Resource Management: Accounting for Interdependence in the Yakima Basin Integrated Plan1. (21st February 2017) - Yoder, Jonathan; Adam, Jennifer; Brady, Michael; Cook, Joseph; Katz, Stephen; Johnston, Shane; Malek, Keyvan; McMillan, John; Yang, Qingqing
Abstract: Integrated water resource management (IWRM) requires accounting for many interrelated facets of water systems, water uses and stakeholders, and water management activities. The consequence is that project analysis must account for the nonseparability among the component parts of IWRM plans. This article presents a benefit‐cost (B‐C) analysis of a set of projects included in the Yakima Basin Integrated Plan proposed for the Yakima Basin in south‐central Washington State. The analysis accounts for interdependence among proposed water storage projects and between water storage and water market development in the context of historical and more adverse projected future climate scenarios. Focusing on irrigation benefits from storage, we show that the value of a given proposed storage project is lower when other proposed storage projects in the basin are implemented, and when water markets are functioning effectively. We find that none of the water storage projects satisfy a B‐C criterion, and that assuring proposed instream flow augmentation is less expensive by purchasing senior diversion rights than relying on new storage to provide it.